2007
DOI: 10.1103/physrevlett.99.046804
|View full text |Cite
|
Sign up to set email alerts
|

Weak-Localization Correction to the Anomalous Hall Effect in Polycrystalline Fe Films

Abstract: In situ transport measurements have been made on ultrathin (<100 A thick) polycrystalline Fe films as a function of temperature and magnetic field for a wide range of disorder strengths. For sheet resistances Rxx less than approximately 3kOmega, we find a logarithmic temperature dependence of the anomalous Hall conductivity sigmaxy, which is shown for the first time to be due to a universal scale dependent weak-localization correction within the skew-scattering model. For higher sheet resistance, granularity b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
65
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 19 publications
8
65
1
Order By: Relevance
“…The nonzero prefactors A xy suggesting that the weak electron localization correction to G AH is present. The smaller coefficients A R and A AH at t=2 nm can be attributed to its large R xx at 5 K [12,14]. In contrast, a universal scaling 2A R ≈A AH is observed at t=5 nm, indicating that the quantum correction to G AH is negligible.…”
Section: R T R Tmentioning
confidence: 82%
See 3 more Smart Citations
“…The nonzero prefactors A xy suggesting that the weak electron localization correction to G AH is present. The smaller coefficients A R and A AH at t=2 nm can be attributed to its large R xx at 5 K [12,14]. In contrast, a universal scaling 2A R ≈A AH is observed at t=5 nm, indicating that the quantum correction to G AH is negligible.…”
Section: R T R Tmentioning
confidence: 82%
“…It should be noted that both calculation [18] and experimental [12] results have demonstrated that there was no interaction-induced lnT correction to G AH . The nonzero prefactors A xy suggesting that the weak electron localization correction to G AH is present.…”
Section: R T R Tmentioning
confidence: 99%
See 2 more Smart Citations
“…effect is the anomalous Hall effect in ferromagnetic granular materials [11]. Now we briefly outline the model and method used to derive the announced results, details of our calculations will be presented elsewhere [12].…”
mentioning
confidence: 99%